Habitudes, conceptions familiales de jeu et situation de jeu symbolique mère-enfant - Butty, Jeanine (My University, 2007)
The framework of our inquiry is a research project that concerns children and mothers consulting a speech and language therapist, with the aim to better understand the inner resources of the child and his surroundings. In order to assess these resources, children and mothers were filmed in a situation of symbolic play. The mothers were questioned to learn more about familial habits and the mother’s preconceptions about playing; based on these replies, we tried to establish "profiles of play" for children and mothers. Then, we analysed some aspects of the play interactions and tried to identify links between the two types of data. Our analysis tends to show that mothers expectations in the play situation, as well as their involvement as real play partners, can lead to real differences in the way they lead the play interaction.